Looking into what makes Muslim millennial and generation Z want to use digital wallets in Banjarmasin - Humaida Humaida; Zaki Mubarak; Rahma Yuliani (ITB AAS INDONESIA Surakarta, 2023)
Digital wallets are one of the solutions given by firms in the fintech industry to support cashless and non-card payments. However, research on digital wallets is still in shortage, and they are needed to continue the expansion of fintech in Indonesia. Even though it is relatively new in financial technology, the DANA digital wallet is already giving other forms of digital payment that have been around for some time a run for their money. DANA can successfully design and improve its various innovative features to attract potential customers in the future. This research aims to determine factors that motivate Muslim millennials and generation Z to use DANA digital wallets. Quantitative approaches are employed in this study through questionnaires for data collection and analysis using multiple regression. Muslim dana digital wallet users between the ages of 18 and 35 from the city of Banjarmasin served as the sample population for this analysis. Meanwhile, one hundred people participated in the study as the sample size. The findings revealed that the users' lifestyles primarily influence the adoption of digital wallets among Banjarmasin's Muslim millennials and generation z populations.